2018
DOI: 10.1055/s-0038-1625985
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Preferences and Concerns among Venous Thromboembolism Patients

Abstract: Background: Warfarin and direct oral anticoagulants (DOACs) are used for the initial treatment and secondary prevention of venous thromboembolism (VTE), and have similar efficacy. Patient concerns and preferences are important considerations when selecting an anticoagulant, yet are not well studied. Methods: VTE patients (n = 519) were surveyed from online sources [clotconnect.org, stoptheclot.org and National Blood Clot Alliance Facebook followers (n = 495)], and a hematology clinic in Vermont (n = 24). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
(41 reference statements)
0
29
1
Order By: Relevance
“…The same was true for patients treated for VTE, who held greater concerns for recurrent VTE risk (519 participants from 1 study; moderate certainty). 52 Studies also suggested that, although the majority of patients treated for VTE would like to avoid adverse events, only 21% to 25% are afraid of hemorrhagic events. Moreover, 87% of patients who had experienced a negative episode reported being "not afraid of" negative consequences (1019 participants from 4 studies; moderate certainty) 29,35,42,52 ( Table 3).…”
Section: Nonutility Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same was true for patients treated for VTE, who held greater concerns for recurrent VTE risk (519 participants from 1 study; moderate certainty). 52 Studies also suggested that, although the majority of patients treated for VTE would like to avoid adverse events, only 21% to 25% are afraid of hemorrhagic events. Moreover, 87% of patients who had experienced a negative episode reported being "not afraid of" negative consequences (1019 participants from 4 studies; moderate certainty) 29,35,42,52 ( Table 3).…”
Section: Nonutility Resultsmentioning
confidence: 99%
“…52 Studies also suggested that, although the majority of patients treated for VTE would like to avoid adverse events, only 21% to 25% are afraid of hemorrhagic events. Moreover, 87% of patients who had experienced a negative episode reported being "not afraid of" negative consequences (1019 participants from 4 studies; moderate certainty) 29,35,42,52 ( Table 3). Similarly, studies including cancer patients and patients with cancer-related thrombosis suggest "the interference with cancer treatment" is the most important attribute influencing their preferences for the medication, followed by "efficacy of the VTE treatment" and "the risk of major bleeding" (509 participants from 2 conjoint analyses; moderate certainty) 46,54 (Table 3).…”
Section: Nonutility Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, patient's preference is among key determinants to decide on extended treatment. Since patients are generally more concerned about recurrent VTE than bleeding, this may stimulate prescribing extended treatment [19].…”
Section: Discussionmentioning
confidence: 99%